Effects of Anti-Inflammatory Agents on Expression of Early Responsive Inflammatory and Catabolic Genes in Ex Vivo Porcine Model of Acute Knee Cartilage Injury. (July 2018) - Genemaras, Amaris A.; Ennis, Hayley; Bradshaw, Brad; Kaplan, Lee; Huang, C.-Y. Charles
Objective: Early intervention therapies targeting inflammation and cell death during the acute phase of cartilage injury have the potential to prevent posttraumatic osteoarthritis. The objective of this study was to investigate the effects of interleukin receptor antagonist protein (IRAP), hyaluronan (HA), dexamethasone (DEX), and mesenchymal stem cell (MSC) treatment on the expression of established genetic markers for matrix degradation, apoptosis, and inflammation in articular cartilage during the acute phase of injury. Design: A custom impact device was used to create replicable injury ex vivo to intact porcine knee joint. One hour after impact, IRAP, HA, DEX, or MSCs was intra-articularly injected. At 8 hours postinjury, cartilage and meniscus samples were harvested for genetic expression analysis. Expression of miR-27b, miR-140, miR-125b, miR-16, miR-34a, miR-146a, miR-22, ADAMTS-4, ADAMTS-5, MMP-3, IL-1β, and TNF-α was analyzed by real-time polymerase chain reaction. Results: At 8 hours postinjury, expression of ADAMTS-4, ADAMTS-5, MMP-3, IL-1β, and TNF-α in cartilage was significantly decreased in IRAP- and DEX-treated joints as compared to nontreated injured joints, whereas only IRAP upregulated expression of miR-140, miR-125b, miR-27b, miR-146a, and miR-22 in cartilage. HA and MSC treatments had no significant effects on catabolic and inflammatory gene expression in cartilage. However, HA treatment significantly upregulated expression of all miRNAs except miR-16. In addition, the treatments tested also exhibited significant influences on meniscus. Conclusions: This study provides a valuable starting point for further research into potential targets for and efficacy of various early intervention strategies that may delay or prevent the progression of posttraumatic osteoarthritis after acute cartilage injury.